Mengkaji Gerakan Sosial Dalam Penyelesaian Kasus Pelanggaran Hak Asasi Manusia Di Indonesia: Studi Kasus Aksi Kamisan Melalui Perspektif Aktor Non-Negara - Alfian Tegar Nur Fauzi; Teza Yudha; Lina Aryani (CV. ULIL ALBAB CORP, 2025)
Kamisan Action is a revolution of a symbolic social movement, on the delivery of demands for injustice in resolving human rights cases in Indonesia by the government. The need to view Kamisan Action as a social movement through the perspective of non-state actors, namely outside the structure of government or state. This study is based on: 1) The unresolved gross human rights violations in Indonesia; 2) The failure of the Indonesian government to resolve human rights violation cases; 3) Allegations that the government is making impunity efforts in resolving gross human rights cases in the past. The research method used is a qualitative case study. The analytical tool in this study uses the theory of social movement dynamics through the perspective of McAdam, McCarthy, and Zald, which consists of: 1) political opportunities (political opportunities); 2) mobilization structure (mobilization structure); and 3) cultural framing (cultural framing). The results of the study concluded that the political opportunities for the demands of the Kamisan action were getting smaller due to obstacles in the process of resolving the case. Then the efforts to mobilize the masses were successful, the Kamisan action masses had spread to various regions. However, the political mobilization carried out by the Kamisan action was still unable to resolve human rights cases in Indonesia. And finally, the framing of the Thursday action has succeeded in portraying its movement as a consistent symbolic action in fighting for the resolution of human rights cases in Indonesia. Then the movement against impunity became the image brought up by the Thursday action masses which was aimed at ensuring that human rights cases continue to run on the convention track. The handling of human rights cases that seemed to ignore the government killed the values ​​of good governance, where there must be open spaces for civil society, because in reality, in the process, democratic values ​​guarantee the rights of citizens.)